Analisis Promosi Dan Harga Terhadap Keputusan Pembelian Di DD Kuliner - Feni Andriani; Sri Emawati (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
The level of intense competition between companies causes companies to really think about the right strategy in facing competition in order to win the hearts of their consumers, so that consumers will decide to buy products sold in that place. This study aims to determine and analyze the effect of promotion and price on purchasing decisions at DD culinary Bima City. This research is an associative type, with the population used in this study, namely all consumers who have purchased products at DD Culinary Bima City whose number is not known with certainty. The number of samples in alternative research amounted to 50 respondents. The sampling technique was carried out by purposive sampling method. The research instrument used in collecting data was a questionnaire with a Likert scale which was given a score of 1 to 5. This research is an associative type with quantitative data from primary data sources. The data analysis technique used is validity test, reliability test, classical assumption test, regression analysis, correlation, determination test and t test. The results of the t-test and f-test showed that product purchasing decisions at DD Culinary Bima City could be influenced by the promotions carried out and the prices set by the Bima City Culinary DD.